Contribution risk towards historical conservation project / Muhammad Daniel Abd Manap and Mohd Nurfaisal Baharuddin - Abd Manap, Muhammad Daniel; Baharuddin, Mohd Nurfaisal (2019)
Heritage building contribute in our economic through the tourism industry and it is challenging to preserve and converse our cultural heritage that have high significance value that reflect our nation. The purpose of this paper is to identify the challenges and risk could happen in building conservation that would affect the successfulness of the project and recommend the best risk management approach can be implemented in heritage building conservation. Risk management in conservation projects had been poorly implemented and practiced in our industry. Conservation projects involve complex process and method where it cannot accurately determine the risk and uncertainty could happen without any experience or knowledge within this field. The methodology applied in this paper by refer the secondary data from articles, journal, and book. Based on the secondary data is to identified contribution factors in building conservation that derive to risk and uncertainty. The identification of contribution factor facilitates conservation practitioners to implement the risk management approach to manage the risk occur during conservation projects.